Impact of the pneumococcal 10-valent vaccine on reducing hospitalization for community-acquired pneumonia in children - Sandra Rodrigues da Silva; Luane Marques de Mello; Anderson Soares da Silva; Altacílio Aparecido Nunes
Abstract Objective: To describe and analyze the occurrence of hospitalizations for community-acquired pneumonia in children before and after the pneumococcal 10-valent conjugate vaccine implementation into the National Immunization Program. Methods: This is an ecological study that includes records of children younger than one year old, vaccinated and not vaccinated with the pneumococcal 10-valent conjugate vaccine in the periods pre- and post-inclusion of the vaccine in the National Immunization Program in the area covered by the Regional Health Superintendence of Alfenas, state of Minas Gerais, Brazil. Vaccination was considered as the exposure factor and hospitalization for community-acquired pneumonia as the endpoint, using secondary annual data by municipality. The prevalence ratio and its 95% confidence interval (95%CI) were used to verify the association between variables. The Z test was used to calculate the difference between proportions. Results: Considering the 26 municipalities of the Regional Health Superintendence of Alfenas, there was a significant reduction in hospitalizations for community-acquired pneumonia in children younger than one year of age, with prevalence ratio (PR)=0.81 (95%CI: 0.74-0.89; p<0.05), indicating a 19% lower prevalence of hospitalization for community-acquired pneumonia in the post-vaccination period. Conclusions: The results suggest the effectiveness of the pneumococcal 10-valent conjugate vaccine in preventing severe cases of community-acquired pneumonia in children younger than one year of age.